2022
DOI: 10.1002/etc.5264
|View full text |Cite
|
Sign up to set email alerts
|

Soil Contamination and Bioaccumulation of Heavy Metals by a Tropical Earthworm Species (Alma nilotica) at Informal E‐Waste Recycling Sites in Douala, Cameroon

Abstract: Soil contamination at electronic waste (e‐waste) recycling sites is pervasive, though many locations have yet to be studied. While such contamination can present risks to soil organisms, little is known on the risks to native species. The objective of the present study was to assess soil contamination by heavy metals at e‐waste recycling sites, and the potential of Alma nilotica, a native earthworm species, to bioaccumulate these metals. Soil samples collected from eight informal e‐waste recycling sites and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Lanno et al ( 2019) also reported over 10-fold difference in Pb BAFs in earthworms across 6 soil treatments. Although Pb and Cr showed up as the more bioaccumulative metals, Alma nilotica is capable of quickly eliminating them when taken out of the contaminated medium unlike Cu and Zn which are only slowly eliminated (Nfor et al, 2022b). No correlation was found between the BAFs and the metal concentrations in either the soil or earthworms.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Lanno et al ( 2019) also reported over 10-fold difference in Pb BAFs in earthworms across 6 soil treatments. Although Pb and Cr showed up as the more bioaccumulative metals, Alma nilotica is capable of quickly eliminating them when taken out of the contaminated medium unlike Cu and Zn which are only slowly eliminated (Nfor et al, 2022b). No correlation was found between the BAFs and the metal concentrations in either the soil or earthworms.…”
Section: Resultsmentioning
confidence: 89%
“…In Cameroon, for example, increased environmental contamination with heavy metals continues to be a subject of major concern. Studies conducted in various localities of the country (Defo et al, 2015;Mofor et al, 2017;Blanchard et al, 2018;Nfor et al, 2022a;Nfor et al, 2022b) have revealed soils contaminated with heavy metals at non-negligible levels from various anthropogenic activities including mining, industrial activities, addition of chemical fertilizers and pesticides, as well as transportation, dumping and discharge of waste electrical and electronic equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Earthworms bioaccumulate toxic substances from the soil substrate in their body tissues [84,85]. This process is pertinent to food safety because human industrial activities have released a number of toxic chemicals into the soil which pose a risk to human health should they enter the food chain [86].…”
Section: Foraged Earthworms May Be Harmful For Humansmentioning
confidence: 99%
“…The average daily intakes (ADI mg/kg/day) were determined by the following Equation according to Nfor et al 12 :…”
Section: Exposure Assessmentmentioning
confidence: 99%